Behavior of oil droplets at the membrane surface during crossflow microfiltration of oil–water emulsions - Tummons, Emily N. (2017)
A fundamental study of microfiltration membrane fouling by emulsified oil was conducted using a combination of real-time visualization, force balance on a droplet, and permeate flux analysis. The model 0.1% v/v hexadecane-in-water emulsions contained sodium dodecyl sulfate (0.1 mM, 0.4 mM, or 0.8 mM) to regulate interfacial tension. Direct Observation Through the Membrane tests with Anopore